变流教师和新加坡华文教育的文化危机 ：以1980、90年代中英报刊的论述和张挥小说为例 = On converted teachers and the cultural crisis of Singapore's Chinese education : through the discourse of 1980s, 90s news articles and Cheong Hui's fictions - 丁之祈 Teng, Zhi Qi (Nanyang Technological University, 2021)
1980年代，新加坡政府宣布将于自1960年推行的双语教育政策中，将重心转向英语。尔后，全国学校实行统一语文源流，指定第一语文为英文，第二语文为母语。在教育制度改革和家长倾向将孩子送进英文源流学校的转变下，华文源流学校陆续关闭，对于华文源流教师的需求锐减而产生过剩。部分华文源流教师因此需参加英语训练课程，并被重新调派至英文源流学校以英语教学，成为“变流教师”。 曾任职“变流教师”的张挥，以1980年代教育制度改革为历史背景，创作出多部作品。其中多篇涉及“华文教育问题”，包括“变流教师”因制度改革而面临的挑战、华文文化式微等。本文通过剖析小说中的象征意象，及其所反映出的教育问题，借此探讨新加坡华文教育的文化危机。本文后半部则通过对照与解析：（一）张挥多篇小说中的‘教师’、‘学生’、‘学校’与‘家长’等各方关系；（二）张挥在与笔者的电邮采访中对于“变流教师”处境的亲身论述和（三）1980，90年代中英文报刊论述，以窥探当时“变流教师”的困境。旨在借由文学作品中的呈现、当事者的真实论述以及报刊论述之间的矛盾与交锋，建构出1980，90年代新加坡“变流教师”和华文教育的文化危机更完整的历史面貌。 The bilingual education policy has been implemented in Singapore by the PAP government since the 1960s. In the 1980s, it was announced that the emphasis will be shifted towards the English Language, alongside the introduction of the New Education System. Concurrently, as parents became more inclined to send their child to English-stream schools, Chinese-stream schools experienced a rapid and sharp decline, contributing to a reduced demand for and hence surplus of Chinese Language teachers. Some Chinese Language teachers from these Chinese-stream schools underwent English Language retraining courses and were redeployed to English-stream schools to teach using the English medium. Such teachers are known as ‘converted teachers’. Cheong Hui was once a ‘converted teacher’ himself, and has written many works, mainly on the historical background of the education system reforms of Singapore in the 1980s. Many of his works involved ‘educational issues’, such as that of difficulties faced by ‘converted teachers’ in adapting to the education system reforms, and that of the declining societal status and standards of the Chinese Language locally. This essay will begin by dissecting the symbols and imagery used in Cheong’s fictions, and the educational issues that they reflect, in a bid to discuss the cultural crisis faced by local Chinese education. The essay goes on to compare and analyse the different perspectives of the teacher, student, school, and parents, as portrayed in Cheong’s fictions; an actual recount of the ‘converted teacher’ experience through an email interview with Cheong himself; and the discourse of newspaper articles in the 1980s and 90s, hence probing into the difficulties faced by ‘converted teachers’ then. Through the comparison of the various perspectives, the essay attempts to present a more well-rounded perspective of the experiences of ‘converted teachers’ and Singapore’s Chinese education and cultural crisis.